Analysis of Motivation, Work Discipline and Work Environment on the Performance of Nganjuk Regency Environmental Service Employees - Aprillia, Dita Damayanti; Leksono, Poniran Yudho (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: The aim of this research is to deepen the understanding of the influence of motivation, discipline and work environment on employee performance. Design/Method/Approach: The approach used in this research is a quantitative approach with a positivist design. Data for the process of filling out questionnaires from respondents and using the SPSS application for calculations as a method. The population used was all employees and the samples obtained were 127 samples. Research Finding: Research findings in multiple regression analysis show that Motivation (X1), Work Discipline (X2), and Work Environment (X3) partially influence the dependent variable (Y), namely Employee Performance. Meanwhile, the Ha test simultaneously means that Work Discipline (X2), Work Environment (X3), and Motivation (X1), have an effect on Y on Employee Performance. Motivation has a good and big influence on performance, research shows that work discipline has a real and significant influence. Work discipline has a significant effect on good employee performance. Theoretical contribution/originality: This research will be useful to help agencies and can increase the reader's insight and knowledge in making decisions. Research Limitations: The research is limited to predetermined variables which only discuss work discipline, motivation and the work environment of performance managers at the Environmental Service.